Longitudinal change of serum exosomal miR-186-5p estimates major adverse cardiac events in acute myocardial infarction patients receiving percutaneous coronary intervention - Ren, Lingyun; Liu, Wei; Chen, Shanshan; Zeng, Haibo (Frontiers in Cardiovascular Medicine, 2024)
Objective: Our recently published study discovers that exosomal microRNA (miR)-186-5p promotes vascular smooth muscle cell viability and invasion to facilitate atherosclerosis. This research aimed to explore the prognostic implication of serum exosomal miR-186-5p in acute myocardial infarction (AMI) patients receiving percutaneous coronary intervention (PCI).Methods: One hundred and fifty AMI patients receiving PCI and 50 healthy controls (HCs) were screened. Serum exosomal miR-186-5p was detected by reverse transcriptase-quantitative polymerase chain reaction assay in AMI patients at admission and after PCI, as well as in HCs after enrollment. Major adverse cardiac events (MACE) were recorded during follow-up in AMI patients receiving PCI.Results: Serum exosomal miR-186-5p was raised in AMI patients versus HCs (P<0.001). Besides, serum exosomal miR-186-5p was positively linked to body mass index (P=0.048), serum creatinine (P=0.021), total cholesterol (P=0.029), and Creactive protein (P=0.018); while it was reversely linked with estimated glomerular filtration rate (P=0.023) in AMI patients. Interestingly, serum exosomal miR-186-5p was correlated with the diagnosis of ST-segment elevation myocardial infarction (P=0.034). Notably, serum exosomal miR-186-5p was decreased after PCI versus at admission (P<0.001). The 6-, 12-, 18-, and 24-month accumulating MACE rates were 4.5%, 8.9%, 14.8%, and 14.8% in AMI patients. Furthermore, serum exosomal miR-186-5p ≥3.39 (maximum value in HCs) after PCI (P=0.021) and its decrement percentage